Sedation by nitrous oxide vs general anestesia in oral surgery: pros and cons. A literature review - Tasso, Alice Cavalvanti (2022)
The nitrous oxide is a colorless gas that, when inhaled, causes depression to the Central Nervous System (CNS), it has an analgesic effect, making the patient, even if conscious, more susceptible to the procedure. On the other hand, general anesthesia causes loss of consciousness and can be obtained through intravenous or inhalation substances, or through a combination of the two. This article aimed to carry out a literature review to present the characteristics and discuss the pros and cons of the mentioned techniques. It was seen that sedation with nitrous oxide is safe and flexible, as it manages to gradually dose the gas release and change the depth of sedation, in addition to allow a quick start and, consequently, a quick end of action. The disadvantage associated with this technique is related to the effect of the gas, which is individual and variable for each organism, and can cause side effects such as nausea and vomiting. The general anesthesia technique, on the other hand, has the positive differential of ensuring oropharyngeal tamponade throughout the procedure, in addition to allowing more extensive procedures in a single session. Its negative points are associated with possible postoperative delirium and its high cost, in addition to the fact that, when compared with conscious sedation, the risks of morbidity and mortality are higher. It was concluded, therefore, that the two techniques have their clear indications, where there is no absolute advantage for opting exclusively for just one. The choice must be made according to the profile of each patient and the surgical approach to be performed.